Differential spectroscopy and beer ageing - Savel, Jan (BrewingScience, 2004)
The role of quinones in the beer oxidation was studied by both differential spectroscopy and photobleached methylene blue reoxidation. Juglone, p-benzoquinone and ubiquinone 0 were added to beer that was pasteurised in the presence or absence of oxygen. Quinones had catalytic effect in the course of beer oxidation by air. Oxygen is consumed by beer in a short time but beer ageing continues in the absence of oxygen. Possible anaerobic mechanism of beer ageing may involve oxidative action of quinones or peroxides, anaerobic Fenton reaction or additional effect of oxygen ingress through crown.